2012
DOI: 10.1111/j.1750-3841.2012.02954.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Enterotoxigenic Staphylococcus aureus in Raw Milk and Dairy Products by Multiplex PCR

Abstract: The aim of this study was to investigate the prevalence of enterotoxigenic Staphylococcus aureus in 122 samples, including 60 raw milk, 32 white cheese, 10 kashar cheese, 10 butter, and 10 ice cream samples obtained from Samsun province, Turkey. In this study, S. aureus was detected in 64 samples, including raw milk (45/60; 75%), white cheese (12/32; 37.5%), kashar cheese (3/10; 30%), butter (3/10; 30%), and ice cream (1/10; 10%) samples. A total of 81 isolates were identified as S. aureus by PCR with the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
2
19
1
Order By: Relevance
“…Milk, dairy products (cheese, ice cream), meats (beef, pork, turkey, chicken), eggs and egg products, and aquatic products are usually described as contaminated with S. aureus (Can and Çelik, 2012; Crago et al , 2012; Gücükoğlu et al , 2012; Gücükoğlu et al , 2013; Gündoğan et al , 2006; Hanson et al , 2011; Hu et al , 2013; Normanno et al , 2007; Pereira et al , 2009; Tang et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Milk, dairy products (cheese, ice cream), meats (beef, pork, turkey, chicken), eggs and egg products, and aquatic products are usually described as contaminated with S. aureus (Can and Çelik, 2012; Crago et al , 2012; Gücükoğlu et al , 2012; Gücükoğlu et al , 2013; Gündoğan et al , 2006; Hanson et al , 2011; Hu et al , 2013; Normanno et al , 2007; Pereira et al , 2009; Tang et al , 2015). …”
Section: Introductionmentioning
confidence: 99%
“…Thus, even if the bacteria are killed, e.g., by heat treatment, the heat-resistant enterotoxins can persist, leading to staphylococcal food poisoning (SFP) (6,8). A notable example is staphylococcal enterotoxin D (SED), which is clearly involved in both cheese official controls performed in France (9) according to European Union regulation 1441/2007 (10) and in SFP outbreaks (11)(12)(13)(14)(15)(16)(17). The sed gene is carried by a plasmid (6,18,19) and controlled by two regulators, the accessory gene regulator (agr) quorum-sensing system, a main regulatory system controlling virulence gene expression in S. aureus (6,12,20) and the staphylococcal accessory regulator sarA (21).…”
mentioning
confidence: 99%
“…Considering that Kırşehir is a small province (225562 inhabitants in 2015) and animal husbandry is one of the main sources of income of the inhabitants, S. aureus is a risk in all counties of Kırşehir according to these results. S. aureus contamination in various foods in Turkey was reported as 57.3% in the Kayseri province (Ertaset al, 2010), 33.4% in Kütahya and Eskişehir region, (Guvenet al, 2010), 13.8% in the Marmara region (Aydin et al, 2011), 6% in Ankara province (Can and Çelik, 2012), 52.5% in Samsun province (Gücükoğlu et al, 2012). The variation of these results was owing to the fact that these studies were conducted on different sample sizes and different food groups.…”
Section: Resultsmentioning
confidence: 79%
“…Although the rate of raw milk sample contamination was similar to their study, the controversy was originated from sample region. Another study was reported even more contamination rate (75%) in raw milk in Samsun province (Gücükoğlu et al, 2012). The high contamination rates of raw milk samples in Turkey reveals the significance of this pathogen in dairy animals.…”
Section: Resultsmentioning
confidence: 99%